From State Control to Societal Governance: Fostering Private Enterprise and Societal Autonomy in Vietnam's Administrative Reforms - Vu Minh, Chau (Westscience Press, 2025)
Vietnam's transition from a centrally planned economy to a market-oriented system has necessitated fundamental changes in administrative governance structures. This paper examines the paradigm shift from direct state control toward societal governance models and analyzes how these reforms impact private enterprise development and societal autonomy. Through qualitative analysis of policy documents, legal frameworks, and expert perspectives, this research explores the mechanisms underlying Vietnam's transition from pre-emptive licensing (tiền kiểm) to post-audit supervision (hậu kiểm) while embracing a developmental state (nhà nước kiến tạo phát triển) approach. The study reveals that while significant progress has been made in reducing direct state intervention, the full realization of societal governance requires deeper institutionalization of participatory mechanisms, enhanced legal frameworks for self-regulation, and strengthened societal autonomy through diversified administrative law sources and robust freedom of association. The findings contribute to understanding state transformation in transitional economies and provide policy recommendations for balancing state guidance with societal self-governance in developing contexts.